Modelling of electronics heat sink – influence of the wake function generation on the accuracy of CFD analysis - Ahmed, Mirghani Ishak; Ismail, Ahmad Faris; Abakrb, Yousif A. (IIUM Press, 2011)
Cooling of electronic components continues to attract many research & development activities towards achieving an effective way of cooling. On this work, an analytic analysis of the cooling process was conducted to calculate the rcquired cooling rate. A Fluent CFD model was developed to model and simulate the system. Experimental results were then used to test and evaluate the conditions at which the software results are approaching the exact measured values. A relation was discovered between the thermal wake function and capability of the software to give better estimations of the circuit board temperatures. The obtained results generally showed good agreement between the simulation and the experimental results.